Pathways and consequences of dissolved organic matter transformation in tropical coastal waters - Nichols, Robert Scott (Nanyang Technological University, 2022)
Tropical coastal waters receive some of the largest fluvial inputs of dissolved organic matter (DOM) globally, acting as a substrate for heterotrophic microbes and as a source of nutrients to marine systems. The cycling of this organic matter depends on its lability to biotic or abiotic degradation processes, which in turn has consequences for processes such as the regeneration of nutrients which sustains primary production, and coastal acidification through the remineralization of organic carbon to CO2. In the first project, we assessed the potential for using phenol oxidase (POx) activity as a proxy of terrestrial dissolved organic carbon biodegradation across peat-draining rivers and coastal waters of Sarawak, Borneo, and report experimental measurements of microbial terrestrial dissolved organic carbon remineralization rates from this region. Our results suggest that direct microbial respiration is perhaps not a major pathway for peatland terrestrial dissolved organic carbon remineralization in Southeast Asia. In the second project, we measured alkaline phosphatase (AP) activity both in the water column and associated with three coral species and their mucus at coral reefs in Singapore as an index of the rate of dissolved organic phosphorus cycling. Our results show that water column AP activity was consistently high, averaging 9 ± l0 nmol L-1 h-1, but was not correlated with dissolved phosphate or other biogeochemical parameters. Coral AP activity ranged from 12–l63 µmol m-2 h-1 depending on species and was equivalent to the AP activity in several meters of overlying water. In the third project, we report data from six bioassays of CO2 and nutrient amended seawater containing natural tropical coastal plankton communities, during two biogeochemically distinct monsoonal seasons in Singapore. Elevated CO2 enhanced phytoplankton growth and increased particulate C:N ratios under nutrient-replete conditions but did not have a significant effect on size structure, growth, or stoichiometry under low nutrient conditions. The heterogeneity of our results between monsoon seasons and incubations highlights how planktonic responses to elevated CO2 concentrations are dependent on multiple interactive factors, such as the availability of nutrients and the phytoplankton community’s ability to acclimate to changes in light and temperature.